Effects of host age and density on the performance of Apanteles hemara (Hymenoptera: Braconidae), a larval endoparasitoid of Spoladea recurvalis (Lepidoptera: Crambidae) - Othim, S.T.O.; Ramasamy, S.; Kahuthia-Gathu, R.; Dubois, T.; Ekesi, S.; Fiaboe, K.K.M. (Oxford University Press, 2019)
The amaranth leaf-webber, Spoladea recurvalis (Fabricius; Lepidoptera: Crambidae), is a serious pest of Amaranthus sp. in Africa and Asia. Apanteles hemara (Nixon; Hymenoptera: Braconidae) is by far the most important larval endoparasitoid of the amaranth leaf-webber. We examined the effects of host density and age on the biological characteristics of A. hemara. The regression model of the number of hosts supplied to A. hemara against the number of larvae parasitized resulted in a curve corresponding to type II functional response, with a significant increase in the number of hosts parasitized up to the density of 30 hosts before being constant up to 40 hosts. In contrast, the parasitism rate decreased linearly with increasing host densities. Development time, sex ratio, and adult longevity were not significantly affected by host density. The immature parasitoid mortality was significantly higher at higher host densities. Apanteles hemara did not parasitize 7-d-old larvae and beyond, while parasitism was significantly higher among 1- to 2-d-old compared with 3- to 4-d-old larvae. Immature parasitoid mortality was 2.6 times higher in 1- to 2-d-old larvae compared with 5- to 6-d-old larvae. The developmental period of the parasitoid from egg to adult was longest among 1- to 2-d-old larvae and least among 5- to 6-d-old larvae. Nonreproductive mortality was markedly higher among 1- to 2-d-old larvae compared with the older larvae. Adult female A. hemara were significantly larger on 3- to 4-d-old larvae compared with either 1- to 2-d-old or 5- to 6-d-old larvae. We discuss the implications of our results for the interpretation of functional response in parasitoids, mass rearing, conservation, and augmentative biological control of S. recurvalis.